2008
DOI: 10.1152/ajpcell.00314.2007
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of lymphocyte migration and cytokine production by ephrinB1 system in rheumatoid arthritis

Abstract: Although the etiology of early events in rheumatoid arthritis (RA) remains undefined, an anomaly in T cell homeostasis and hyperproliferation of synovial-lining cells are involved in the disease process. Since it has been reported that the ephrin/Eph receptor system plays important signaling roles in inflammation processes, we attempted to examine ephrinB molecules in T cells and synovial cells derived from RA in this study. The expression level of ephrinB1 was significantly high in synovial fibroblasts and CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…These studies showed that DNA methylation can play an important role in various pathways, such as apoptosis and IL-6, CXCL12, and Ephrin-B1 expression in RASF (20)(21)(22). These results prompted us to perform a genome-wide DNA methylation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that DNA methylation can play an important role in various pathways, such as apoptosis and IL-6, CXCL12, and Ephrin-B1 expression in RASF (20)(21)(22). These results prompted us to perform a genome-wide DNA methylation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…1 For example, some axon guidance molecules, such as slits [2][3][4] and ephrins, [5][6][7][8] have been shown to regulate immune cell migration. In addition, T-cell-antigenpresenting cell contact sites, the so-called 'immunological synapse', is structurally similar to the 'neurological synapse' that connects pairs of neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, also in PBMCs and T cells from RA patients disturbances of DNA methylation could be detected [39]. Particularly, in RA PBMCs loss of methylation in the promoter of the IL-6 and the ephrinB1 gene was found to be connected to increased expression of these genes in RA [40,41].…”
Section: Changes Of Dna Methylation In Ramentioning
confidence: 96%